The role of mentoring in leadership development: A qualitative study of upper administration women in the National Basketball Association - Picariello, M.; Angelle, P. S.; Trendafilova, S.; Waller, S.; Ziakas, V. (Journal of Global Sport Management, 2021)
There is a global concern for women underrepresentation in traditionally male-dominated professions, particularly within upper management ranks. A possible strategy for addressing the problem could be effective mentoring. This study contributes to the scholarly literature and understanding of the relationship between mentoring and leadership development for female executives in the context of the National Basketball Association (NBA). The research design for this study was qualitative in nature. Three dominant themes emerged (a) career functions, (b) psychosocial support, and (c) organizational socialization. The findings of this study confirm that women perceive mentoring as a pivotal factor in their careers. Coaching and counseling were the two most important functions in developing a leader. Human resource managers can use these findings to promote a holistic approach to mentoring that may be strategic in terms of talent identification, talent management, talent retention, and leadership development.